A Novel Hand Pallet Truck and Multi-objective Optimization Design of It's Lifting Mechanism. Issue 1 (March 2020) - Yang, Bo; Yuan, Jianhui; Chen, Min; Yu, Fenhua
Abstract: Hand pallet truck is widely used to carry baggage and cargoes in daily life and work. However, rotary-lift based luggage hand pallet truck is inconvenient to handle and difficult to carry heavy goods. Hydraulic cylinder based hand pallet truck is also used commonly, but its lifting speed is not fast enough. In addition, most of them can't save energy. To this end, a novel rotary-lift based hand pallet truck is proposed. Auxiliary and cushioning forces are provided by gas springs. Its lifting height is adjustable. Critically, its lifting mechanism can be locked automatically after ascending or descending into the target positions. Thus, it's easy for just one person to operate. Aiming at saving time, force and energy, a multi-objective optimization design model for the lifting mechanism is built, based on which most key parameters and dynamics indexes can be calculated. Numerical analysis and experiment results show that the proposed model is effective and the design scheme of the novel hand pallet truck is feasible.